Nasogastric and intravenous infusions of (+)-4-propyl-9-hydroxynaphthoxazine (PHNO) in Parkinson's disease. Issue 2 (February 1990) - Coleman, R J; Quinn, N P; Traub, M; Marsden, C D
Abstract : (+)-4-propyl-9-hydroxynaphthoxazine (PHNO) is a new dopamine agonist which is capable of producing a sustained response in parkinsonian patients with "on-off" fluctuations when given as a continuous infusion either nasogastrically or intravenously. These data suggest that a sustained release formulation of PHNO may provide a significant, new treatment for patients with "on-off" fluctuations.